Penanaman Nilai Karakter Peduli Lingkungan Siswa Kelas XI Di SMA Kemala Bhayangkari 3 Porong - Angelin Rosalina Eka Agustin; Suhari Suhari (Jurnal Kajian dan Penelitian Umum, 2023)
Education in Indonesia is now faced with the destruction of the younger generation. The younger generation is now influenced by many things that give rise to a prolonged moral crisis. An example of a moral crisis that often occurs is littering which causes the environment to become dirty. Based on some critical moral examples, it can be proven that a person's behavior in caring for the right environment in this day and age is very weakened. From the various problems that occur, it is necessary to strengthen character education from an early age, especially the character of caring for the environment in order to become a responsible and disciplined person. The purpose of this study is to examine information related to the forms of instillation of character values caring for the environment of students at Kemala Bhayangkari 3 Porong High School widely and thoroughly and also to identify the role of teachers and school residents in strengthening the cultivation of environmentally caring character values of class XI students at Kemala Bhayangkari 3 Porong High School clearly. Researchers in this study used descriptive qualitative methods and for data collection techniques using observation, interview, and documentation methods. The results of this study the author reported that the cultivation of the character value of caring for the environment of class XI students at Kemala Bhayangkari 3 Porong High School has been carried out well as well, always cleaning the classroom, picketting according to the schedule that has been made, the classroom is clean and fragrant, a gift for the class that gets the cleanest class.